A Global Regulatory Network for Dysregulated Gene Expression and Abnormal Metabolic Signaling in Immune Cells in the Microenvironment of Graves’ Disease and Hashimoto’s Thyroiditis - Zheng, Haitao; Xu, Jie; Chu, Yongli; Jiang, Wenzhou; Yao, Wenjie; Mo, Shaowen; Song, Xicheng; Zhou, Jin (Frontiers in Immunology, 2022)
Background: Although the pathogenetic mechanisms of Hashimoto's thyroiditis (HT) and Graves' disease (GD) have been elucidated, the molecular mechanisms by which the abnormal immune function of cellular subpopulations trigger an autoimmune attack on thyroid tissue largely remains unexplained. Methods: The study included 2 HT patients, 2 GD patients, and 1 control donor. The thyroid samples were extracted for single cell RNA sequencing, whole transcriptome, full-length transcriptome (Oxford nanopore technology), and metabolome sequencing. Identification of immune cells with dysregulated gene expression and abnormal metabolic signaling was performed in the microenvironment, both at the bulk and single-cell levels. Based on functional enrichment analysis, the biological processes and pathways involved in abnormal immune cells were further explored. Finally, according to cell communication analysis, the global regulatory network of immune cells was constructed. Results: CD4+ T cells, CD8+ T cells, and macrophages were abnormally increased in patients with HT and GD. The differentially expressed genes of these cells were significantly involved in signaling pathways, including Th1 and Th2 cell differentiation, Th17 cell differentiation, cytokine-cytokine receptor interaction, and NF-kappa B signaling pathway. Moreover, in HT, CD4+ T cells interact with macrophages via the IL16-CCR5/FGF10-FGFR1/CXCL13-CXCR3 axis, and macrophages interact with CD8+ T cells via the CD70-CD27 axis, thereby activating the T cell receptor signaling pathway and NF-kappa B signaling pathway. In GD, CD4+ T cells interact with macrophages via the CXCR3-CXCL10/PKM-CD44/MHCII-NFKBIE axis, and macrophages interact with CD8+ T cells via the IFNG-IFNGR1/CCR7-CCL21 axis, thereby activating T cells receptor signaling pathway, Th1 and Th2 cell differentiation, and chemokine signaling pathway. Conclusion: In HT and GD, immune dysregulated cells interact and activate relevant immune pathways and further aggravate the immune response. This may trigger the immune cells to target the thyroid tissue and influence the development of the disease.